Assessing the Prevalence of Energy Hardship in Canada: An Enhanced Methodology Integrating Energy Modeling - Al Humidi, Sara (University of Waterloo, 2025)
The building sector has focused on addressing climate mitigation through the electrification and decarbonization of households, mainly by upgrading building envelope and replacing combustion-based systems with electric heat pumps. However, the impact of climate change could result in more households falling into energy hardship, underscoring the need for an equitable transition. A household falls under energy hardship if its energy expenditure ratio exceeds the defined threshold, regardless of its total household income. Energy hardship encompasses both energy poverty and energy burden. Thus, a household experiences energy poverty if i) its energy expenditure ratio exceeds the defined threshold and ii) the total household income is below low-income cut-offs. A household experiences an energy burden if i) its energy expenditure ratio exceeds the defined threshold and ii) the total household income is above low-income cut-offs. Techno-economic factors such as energy costs, type of fuel, building age and envelope condition, and type of heating and cooling system in a household contribute to energy hardship. Socioeconomic factors such as income, education, and race are also catalysts to the problem, making energy poverty a multidimensional issue with great implications for public health, social equity, and environmental sustainability. This study aims to quantify energy hardship in Canada in 2019 and 2021 and identify the building and household characteristics experiencing energy poverty. Further analysis was completed for Ontario, Canada to establish a correlation and quantify the impact climate change and household electrification (e.g., switching from a natural gas furnace to a heat pump) have on energy hardship. The study identified key indicators of energy poverty and burden, confirming that household income is the most critical factor. Nearly 40% of Canadian households with an income of CAD$29,000 fall under energy poverty. Older dwellings, which tend to be leaky with poor insulation and outdated HVAC systems, contribute to higher energy consumption. Single-detached homes, with major repair requirements, are likely to be energy burdened (17%). Additionally, socioeconomic factors play a role, one person households (31%) households being the most affected by energy hardship. Education and employment also indirectly impacted energy poverty (10%); households with a higher education and full-time employment were less likely to be energy poor. The Ontario-specific analysis mirrored national trends, revealing that energy burden is more pronounced in rural areas (36%). In addition, an energy simulation study was performed for a median energy-poor household in Ontario. The study investigated two scenarios: a business-as-usual scenario where the households performed minimal energy efficiency upgrades, and an electrification and decarbonization scenario where energy-poor households implemented measures such as envelope renovations and switching to fully electric heating system (i.e., cold climate air source heat pump). The energy modeling results revealed the importance of income levels in alleviating energy hardship. Regardless of the level of energy efficiency measures applied, the median energy-poor household remained in energy poverty after building enclosure and airtightness improvement when maintaining a natural gas furnace or fuel switching to a heat pump (11.2% and 14.3%, respectively), . Households earning CAD$50,000 after tax came out of energy hardship after insulation and airtightness upgrades. However, the adoption of an electric heat pump worsened energy hardship by doubling the costs of electricity despite the fact that reduced energy use intensity by nearly 50%. This concluded that energy efficiency measures alone are not enough to remove households out of energy poverty (or hardship, in general) in Ontario. By analyzing the prevalence, causes, and impacts of energy poverty in Canada and Ontario, this study aims to develop a replicable methodology that provides evidence-based insights to inform policy decisions and support the development of effective interventions that are inclusive and equitable for all households
Keywords: energy hardship; energy poverty; energy burden; decarbonization; electrification; equity